Reliability of self reported smoking status by pregnant women for estimating smoking prevalence: a retrospective, cross sectional study. (29th October 2009) - Shipton, Deborah; Tappin, David M; Vadiveloo, Thenmalar; Crossley, Jennifer A; Aitken, David A; Chalmers, Jim
Abstract : Objective To determine what impact reliance on self reported smoking status during pregnancy has on both the accuracy of smoking prevalence figures and access to smoking cessation services for pregnant women in Scotland. Design Retrospective, cross sectional study of cotinine measurements in stored blood samples. Participants Random sample (n=3475) of the 21 029 pregnant women in the West of Scotland who opted for second trimester prenatal screening over a one year period. Main outcome measure Smoking status validated with cotinine measurement by maternal area deprivation category (Scottish Index of Multiple Deprivation). Results Reliance on self reported smoking status underestimated true smoking by 25% (1046/3475 (30%) from cotinine measurement v 839/3475 (24%) from self reporting, z score 8.27, P<0.001). Projected figures suggest that in Scotland more than 2400 pregnant smokers go undetected each year. A greater proportion of smokers in the least deprived areas (deprivation categories 1+2) did not report their smoking (39%) compared with women in the most deprived areas (22% in deprivation categories 4+5), but, because smoking was far more common in the most deprived areas (706 (40%) in deprived areas compared with 142 (14%) in affluent areas), projected figures for Scotland suggest that twice as many women in the most deprived areas are undetected (n=1196) than in the least deprived areas (n=642). Conclusion Reliance on self reporting to identify pregnant smokers significantly underestimates the number of pregnant smokers in Scotland and results in a failure to detect over 2400 smokers each year who are therefore not offered smoking cessation services.